2014
DOI: 10.2215/cjn.07630713
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis versus Nondialysis in Patients with AKI

Abstract: Background and objectives The benefit of the initiation of dialysis for AKI may differ depending on patient factors, but, because of a lack of robust evidence, the decision to initiate dialysis for AKI remains subjective in many cases. Prior studies examining dialysis initiation for AKI have examined outcomes of dialyzed patients compared with other dialyzed patients with different characteristics. Without an adequate nondialyzed control group, these studies cannot provide information on the benefit of dialysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 34 publications
4
37
0
Order By: Relevance
“…Two other studies (16,17) demonstrated a similar risk of mortality in patients who did or did not receive RRT after matching patients by propensity analysis scoring. In the most recent study, RRT was associated with a better survival only in patients with a high level of serum creatinine (.4.2 mg/dl) (27), leading the authors to speculate that these findings could be explained by metabolic differences between the patients with low and high creatinine levels. However, these studies did not include all of the AKI complications and urine output as adjusted variables.…”
Section: Discussionmentioning
confidence: 99%
“…Two other studies (16,17) demonstrated a similar risk of mortality in patients who did or did not receive RRT after matching patients by propensity analysis scoring. In the most recent study, RRT was associated with a better survival only in patients with a high level of serum creatinine (.4.2 mg/dl) (27), leading the authors to speculate that these findings could be explained by metabolic differences between the patients with low and high creatinine levels. However, these studies did not include all of the AKI complications and urine output as adjusted variables.…”
Section: Discussionmentioning
confidence: 99%
“…Since the majority of patients with AKI never receive RRT in clinical practice, existing studies and analyses provide insufficient guidance on those who should receive RRT. A recent analysis using propensity matching concluded that patients with AKI only clearly benefitted from RRT if they developed severe azotemia (SCr >4.2 mg/dl) [11] . Clearly this leaves the conundrum that patients who are likely to benefit most from RRT are not easy to identify early at a stage when they may benefit most.…”
Section: When Should Acute Renal Replacement Therapy Be Initiated?mentioning
confidence: 99%
“…Vaara et al use a propensity score-based matching strategy to overcome this limitation, a technique employed by a few other groups, including our own (14,15). While we did not find a benefit to early initiation of dialysis (rather, we found that dialysis was preferable to no dialysis when initiated among those with higher serum creatinine concentrations), we did not use the same definition of "early.…”
mentioning
confidence: 76%